(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of the study is to suggest the advanced fluid flow simulation of centrifugal pump that will be implemented in training of maritime specialists. It has been developed numerical simulation using full-cloud CAE simulation software. The study describes how to use rotating zones to run incompressible fluid flow simulation on a centrifugal pump component of turbo equipment. The complexity of this use case results from the requirement of modeling a rotating region. Simulations including spinning regions necessitate additional processes for meshing and modeling the flow, which are discussed in this current study. The main value of that study is that here the task like modeling of the flow behavior of any complex turbo machinery like centrifugal pump is extremely difficult and all this is overcome by clarifying incompressible flow field around Centrifugal pump. Another main advantage of this study is that the results obtained to clarify the flow behavior through the centrifugal pump are applied in the training of students in the disciplines of marine machinery and mechanisms and hydraulics. With the results obtained in this way, which are implemented in the teaching methodology, a visual example is given to the future specialists of ship mechanics by clarifying a practical problem in a complex turbomachinery element such as the centrifugal pump using the methods of modern computing programs.